2021
DOI: 10.1073/pnas.2024446118
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome contributions to altered metabolism in a pig model of undernutrition

Abstract: The concept that gut microbiome-expressed functions regulate ponderal growth has important implications for infant and child health, as well as animal health. Using an intergenerational pig model of diet restriction (DR) that produces reduced weight gain, we developed a feature-selection algorithm to identify representative characteristics distinguishing DR fecal microbiomes from those of full-fed (FF) pigs as both groups consumed a common sequence of diets during their growth cycle. Gnotobiotic mice were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Some studies have used a porcine model to investigate these interactions, because pigs and humans have highly similar physiological activities, such as gut microbiome colonization and metabolic and immune functions ( 14 , 15 ). A previous study revealed that an intergenerational pig model of dietary restriction provided an opportunity to understand which features in the developing pig microbiome were causally linked to regulation of various growth parameters ( 16 ). Recently, a study of the metabolic syndrome (MetS) porcine model by our group indicated that a long-term HED altered the microbiome of gut contents, decreasing levels of butyrate-producing bacteria, including the genus Bacteroides and the families Lachnospiraceae and Ruminococcaceae ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used a porcine model to investigate these interactions, because pigs and humans have highly similar physiological activities, such as gut microbiome colonization and metabolic and immune functions ( 14 , 15 ). A previous study revealed that an intergenerational pig model of dietary restriction provided an opportunity to understand which features in the developing pig microbiome were causally linked to regulation of various growth parameters ( 16 ). Recently, a study of the metabolic syndrome (MetS) porcine model by our group indicated that a long-term HED altered the microbiome of gut contents, decreasing levels of butyrate-producing bacteria, including the genus Bacteroides and the families Lachnospiraceae and Ruminococcaceae ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A full list of metabolites identified by volcano plot is provided in S1 Table. Metabolomics data related to swine, while growing, is fairly limited 42 46 , particularly metabolomics pertaining to piglets in a diseased stated, most of which are serum or tissue based 47 50 . The Human Metabolome Database 51 is much more comprehensive, particularly for diseased states, than the Livestock Metabolome Database 52 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the digestion and absorption of various nutrients, the intestinal tract is also the main place for microbial colonization. There are tens of thousands of microorganisms (including fungi, viruses and bacteria) in the intestinal tract of mammals, which play an important role in maintaining the stability of the intestinal environment and the health of the host ( 30 ). Changes in feed composition may affect the composition of intestinal microorganisms.…”
Section: Discussionmentioning
confidence: 99%